Investigation of wall panel performance using recycled concrete aggregate and perlite as partial replacement for natural fine aggregate under uniformly distributed load - Amir Khomeiny Ruslan; Noorsuhada Md Nor; M. Z. Ruzailan; Amril Hadri Jamaludin; Soffian Noor Mat Saliah; Mohd Azrizal Fauzi; Ahmad Syauqi Md Hassan; Nor Azian Aziz (Penerbit Universiti Kebangsaan Malaysia, 2024)
The increasing depletion of natural resources and the environmental impact of conventional construction practices necessitate the exploration of sustainable alternatives in the construction industry. One promising approach is the use of recycled concrete aggregate (RCA) as a partial replacement for natural fine aggregates in concrete production. However, the performance of RCA in structural applications remains a critical concern, particularly regarding its impact on the mechanical properties of concrete. This study investigates the effects of RCA on the structural performance of wall panels subjected to uniformly distributed loads, with a focus on fresh and hardened properties. Wall panels with dimensions of 1000 mm x 480 mm x 120 mm were produced with RCA replacing 0% and 50% of the natural fine aggregate. The samples were labelled as control (SW120UC) and RCA (SW120U) samples, respectively. In terms of fresh properties, the workability of the control mortar (SW120UC) with 0% RCA was 57%, while the mortar with 50% RCA (SW120U) exhibited a workability of 56%. For hardened properties, the compressive strength of the control cubes (SW120UC) at 28 days was 10.21 MPa, whereas the cubes containing 50% RCA (SW120U) achieved a compressive strength of 16.52 MPa. The maximum load capacity of the RCA wall panels (SW120U) was 90 kN with a stress of 1.6 MPa, compared to 70 kN and 1.2 MPa for the control panels (SW120UC). Furthermore, the highest load versus deflection analysis revealed that SW120U with RCA reached a maximum load of 90 kN with a vertical deflection of 1.49 mm, whereas SW120UC with 0% RCA exhibited a maximum load of 50 kN and a deflection of 0.6 mm. These results demonstrate that RCA can significantly enhance the structural performance of concrete wall panels by improving compressive strength and load-bearing capacity while maintaining acceptable workability.